A educação musical na ONG Corpo Cidadão - Evandro Carvalho Menezes (2009)
This research approaches music education at NGO Corpo Cidadão, located in Belo Horizonte-MG, with children and adolescents living at risk in the capital as well as in Ibirité, town from Belo Horizonte region. The aim of this research was to investigate how is the musical-pedagogical process in the context of that NGO. Hence, this study wanted to investigate how are the actions and interactions between people and their various conceptions of world, values, knowledge and ambitions, therefore linked to the field of sociocultural studies of music education. The research methodology was based on phenomenological perspectives. A case study was carried out with participant observation in different units of Corpo Cidadão, with qualitative approachand semi-structured interviews of the music educators. The data analysis took place from a critical point of view regarding art education in NGOs and its place in the society transformation (MACEDO, 2008); a proposal of a music education which considers the human formation as its main aim and the transformation of art in environmental art or functional art (KOELLREUTTER, 1997, 1998); the comprehension, according to sociology of education perspective, of contemporary socialization as total social phenomena(SETTON, 2007); and a comprehension of music as social practice, of pedagogical-musical process as total social fact and of knowledge production through dynamic of social movements (KLEBER, 2006). The pedagogical-musical practices at NGO pointed to be results of a work that have been built in constantly negotiation with the demands of a collective and interactive context, having performance as a central point of learning process